Correlation and path coefficient analysis for malting quality traits under varying sowing dates in barley (Hordeum vulgare L.) - Goyal, Vishnu Kumar; Kumar, Dinesh; Kharub, Ajit Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2018)
The present study was conducted to delineate association of malting quality traits under timely and late sown conditions in barley. General means for test weight, 1000 grain weight, grain protein content, and hot water extract were exhibited as 60.09 kg/hl, 44.57 g, 11.57 and 79.78 percents, respectively under timely sown conditions. Average diastatic power and FAN content were depicted as 107.90 oL and 178.72 ppm, under late sown conditions. The traits averages for test weight, bold grains, 1000 grain weight, protein content, and FAN content were higher under late sown conditions, due to prolonged grain filling period under congenial climatic conditions. Hot water extract found negatively associated with grain protein (-0.27 and -0.48) and FAN content (-0.15 and -0.27), while positively associated with Kolbach index (0.16 and 0.47) under both the sowing conditions. The quality characters namely test weight and Kolbach index exhibited positive direct effects, while grain protein content, wort filtration rate and FAN content depicted negative direct effects on hot water extract under timely and late sown conditions. Therefore, for better malting quality direct selection for the grain physical parameters viz. test weight and bold grains, while restriction selection model for protein and FAN contents is suggested under timely and late planting dates.Â Doi.org/ 10.25174/2249-4065/2018/84067